Dermatoscopic findings of atrophic dermatofibroma protuberans - Bengu Nisa Akay; Ezgi Unlu; Cengizhan Erdem; aylin Okcu Heper (Mattioli1885, 2015)
Dermatofibrosarcoma protuberans (DFSP) is an uncommon locally aggressive mesenchymal tumor with a high local recurrence rate. Atrophic DFSP is a rare variant of DFSP characterized by a non-protuberant lesion. We report on a 23-year-old female, who presented with an atrophic, asymptomatic macule on the right side of her back 2 cm in diameter. Dermatoscopic examination revealed homogenous pigment network on a purplish erythematous background. The histopathological finding of the incisional biopsy material was consistent with DFSP. To our knowledge, this is the second case of atrophic DFSP discussing the dermatoscopic features of this relatively rare condition.